Chemical contaminants of indoor air quality (IAQ): a review - Mohamed Sunar, Norshuhaila; Parjo, Umi Kalthsom; Subramaniam, Menega; Leman, Abdul Mutalib; Hamidon, Nuramidah; Muhamad, Mimi Suliza; Abdul Hamid, Nor Hazren; Ali, Roslinda (Penerbit UTHM, 2020)
Chemical contaminants are mostly not easy to determine in terms of their source and effect. However, the chemical contaminants in indoor air were identified as gases and vapors (inorganic and organic), and particulates matter [1]. In the indoor air environment, the chemical contaminants access from outdoor or develop within the building. In addition, chemical contaminants can originate anywhere in a facility in excess of recommended amounts [2]. Nowadays all building has some collection of chemical around with potential to become a contaminant in the air. According to DOSH, 2010 [3] stated that the main factor chemical pollutants usually found in the indoor air are carbon monoxide, formaldehyde, respirable particulates, total volatile organic compounds (TVOC). This chapter also presents the basic knowledge of organic and inorganic pollutant as chemical contaminants of Indoor Air Quality (IAQ).